Normative values and factors affecting saphenous nerve responses in a south Asian population: a cross-sectional neurophysiological study at a tertiary care hospital in Pakistan - Hameed, Sajid; Aziz, Bisma; Baig, Pinin; Malik, Marib Ghulam Rasool; Awan, Safia; Khan, Sara (BMC neurology, 2024)
Background The saphenous nerve, a sensory branch of the femoral nerve, is not commonly included in routine lower extremity nerve conduction studies due to a high frequency of non-recordable responses in healthy subjects. However, saphenous nerve conduction studies are sometimes utilized for the diagnostic assessment of isolated lumbosacral plexus, femoral, or saphenous mononeuropathies. Our study aims to determine normative saphenous nerve response values in a healthy Pakistani population and to investigate their associations with patient body mass index, age, and gender. Methods This cross-sectional descriptive study was undertaken over a 3‑month period (May to July 2021) at a neurophysiology department of a tertiary care center in Pakistan. Healthy subjects underwent neurological examination, anthropometric measurements, and bilateral SN nerve conduction studies, with recording of peak-latency, peak-to-peak amplitude and conduction velocity. Statistical analyses and linear regression were conducted to evaluate associations between nerve conduction study variables and patient characteristics. Statistical analyses were also run to assess patient characteristics affecting recordability of saphenous nerve responses. A p-value < 0.05 was considered statistically significant. Results Among 117 subjects, 79.5% ( n = 93) had recordable saphenous nerve responses. Median peak-latency, amplitude, and conduction velocity were 3.2 (3.0-3.3) m/s, 7.7 (5.8–9.9) uV, and 44.0 (42.0–47.0) m/s, respectively. Bilaterally absent responses were observed in 20.5% ( n = 24) of subjects. Obese participants had a significantly higher number of absent saphenous responses ( p = 0.033). Females had shorter peak-latency ( p = 0.006) and higher conduction velocity ( p = 0.012). Conclusions Saphenous nerve responses can be used to assess unilateral femoral and saphenous nerve pathologies, provided they are recordable on the asymptomatic side for comparison. Absent bilateral saphenous nerve responses should be interpreted with caution given their prevalence in healthy individuals. Patient characteristics should be taken into consideration when interpreting recordable and nonrecordable saphenous nerve responses.